Nanoscale pore characteristics of the Jurassic Dongyuemiao member lacustrine shale, Eastern Sichuan Basin, SW China: Insights from SEM, NMR, LTNA, and MICP experiments - Zhou, Yadong; Wang, Zhanlei; Hu, Dongfeng; Wei, Zhihong; Wei, Xiangfeng; Liu, Ruobing; Wang, Daojun; Jiang, Yuqiang (Frontiers in Earth Science, 2023)
The Jurassic Dongyuemiao Member is the most promising target for lacustrine shale gas exploration in Sichuan Basin. By integrating SEM, NMR, LTNA, and MICP experiments, and other basic measurements, the nanoscale pore category and structure and the corresponding controlling factors of Dongyuemiao lacustrine shale in Eastern Sichuan Basin are studied. The results denote that organic pores comprise primary pores within plant debris and secondary pores within bitumen. Inorganic pores are composed of intraparticle pores within calcite particles, intercrystalline pores between pyrite crystals, and interparticle pores between different minerals. The 4th Section lacustrine shale of Dongyuemiao Member has the best pore structure, exhibiting high organic pore proportion, large amounts of gas adsorption, and parallel plate-shaped pore morphology. Micropores (<2 nm) are the main contributors of the pore volume and surface area of Dongyuemiao lacustrine shale. Moreover, the enrichment of organic matter positively affects the formation of micropores and has no influence on the mesopore–macropore (>2 nm). Quartz does not significantly affect the nanoscale pore formation. The intraparticle pores within calcite particles constitute part of mesopore–macropore but not micropores. Clay minerals are conducive to the formation of micropores but play a negative role in the formation of mesopore–macropore.